Strengthening of Character Through Local Wisdom Values in Babad Banyumas - Nur Shofiah, Aji (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
Strengthening the characters become an urgent need, especially in education. This was done in view of the importance of strengthening the character in orde to deal with the moral degradation and shifting cultural values among teenagers today. Moral education is very important for the student to improve intelligence, emotional and spiritual. School arrange creatif Innovations of moral values learning programs in the form of real behavior and attitude, not only conceptual. In this conceptual framework, this paper aims to reinforce the need for the values of local wisdom in building the character of students through a local identity of Babad Banyumas. The focus of this study emphasize the character educational values based on moral in Babad Banyumas that there is can be classified into three core values, such as: 1) social values include politeness, mutual respect, and mutual help. In the Babad Banyumas, this is shown by the attitude of Ki Dipati Kaleng in serve guests; 2) The value of morality includes human actions and also their thoughts and the establishment of what is good and bad, about what is appropriate and inappropriate to do. This is shown by the attitude of Raden Baribin face power conflict with her own brother; 3) The value of religiosity which includes spiritual attitude shown by Dipawijaya the form of asceticism (Khalwat/Tapa Brata) pray gift from God “Hyang Maha Agung” and tradition every friday night face (Sowan) to the King in Keraton followed by a tadarus quran in mosque (Suranatan).